Feinstaub und Brustkrebs (Deutsche Zeitschrift für Onkologie, 2021)
DuPré NC, Hart JE, Holmes MD et al. Particulate matter and traffic-related exposures in relation to breast cancer survival. Cancer Epidemiol Biomarkers Prev 2019; 28: 751–759. doi:10.1158/1055–9965.EPI-18–0803